Psychological Features of Competitive Motivation of Athletes - Juraev Vohidjon Mukhammedovich (Central Asian Journal of Literature, Philosophy and Culture, 2022)
This article discusses ways to increase the motivation of athletes at competitions, control their pre-competitive activities and manage pre-stellar excitement